STRUKTUR DAN POLA IRAMA KESENIAN TALEMPONG BOTUANG DI KENAGARIAN VII KOTO TALAGO KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Ridho Putra; Marzam Marzam; Erfan Erfan (SENDRATASIK UNP, 2018)
Abstract This study aimed to describe the structure and pattern of the Talempong Botuang rhythm. In this research, the structure and rhythmic patterns in the Talempong Botuang art forms would be known, such as Mudiak Arau, Talago Biru, and Kelok Sambilan. This article was compiled based on the undergraduate thesis “The Analysis of Talempong Botuang Art Rhythm Structure and Pattern in Kenagarian VII Koto Talago, Guguak Subdistrict, Lima Puluh Kota Regency”.. This study was classified as qualitative research using descriptive analysis approach. The object of research was Talempong Botuang in kenagarian VII koto Talago Guguak Subdistrict, Lima Puluh Kota Regency. The instruments in this study were the researcher himself and stationery, audio, video, camera. Data collection techniques used in this study included observation, interviews, literature studies, and documentation. Data in this study were obtained by conducting direct observations, interviews, and exercises. The results showed that Talempong Botuang arts basically had the same music structure. Thus, Dendang Mudiak Arau, Talago Biru, and Kelok Sambilan in Talempong Botuang art had similarities in performance patterns, and the rhythm pattern used was not 1/16 so that the art Talempong Botuang had a rapid performance. Keywords: Structure, Pattern, Rhythm